Bibliometric analysis of portfolio diversification focusing on alternative investments - Hristovski Goran; Gockov Gjorgji; Merdzan Gjunter (Ekonomski Anali)
Portfolio diversification, a key investment management strategy, traditionally involved stocks, bonds, and cash. However, the growing complexity of financial markets has led to increased interest in alternative investments such as hedge funds, private equity, real estate, commodities, and cryptocurrencies due to their low correlations with traditional assets. This study aims to explore the evolving role of alternative investments in portfolio diversification by conducting a bibliometric analysis of 405 articles from the Web of Science database. The analysis provides insights into the most frequently cited articles, journals, co-author teams, individual authors, organisations, and countries. Additionally, it includes sentiment analysis of abstracts, followed by keyword co-occurrence, bibliographic coupling, and co-citation analysis. The findings reveal a marked increase in research activity on alternative investments over the past five years, peaking in 2019. Key themes identified include portfolio optimisation, asset allocation, and the integration of traditional and alternative investments, underscoring the growing significance of alternative assets in modern investment strategies. These findings have implications for both the academic community and practitioners, enhancing the understanding of alternative investments in portfolio diversification and informing future research and investment strategies.